Spherical Nucleic Acids with Tailored and Active Protein Coronae - Zhang, Wuliang (ACS Cent Sci, 2019)
[Image: see text] Spherical nucleic acids (SNAs) are nanomaterials typically consisting of a nanoparticle core and a functional, dense, and highly oriented oligonucleotide shell with unusual biological properties that make them appealing for many applications, including sequence-specific gene silencing, mRNA quantification, and immunostimulation. When placed in biological fluids, SNAs readily interact with serum proteins, leading to the formation of ill-defined protein coronae on the surface, which can influence the targeting capabilities of the conjugate. In this work, SNAs were designed and synthesized with functional proteins, such as antibodies and serum albumin, deliberately adsorbed onto their surfaces. These particles exhibit increased resistance to protease degradation compared with native SNAs but still remain functional, as they can engage in hybridization with complementary oligonucleotides. SNAs with adsorbed targeting antibodies exhibit improved cellular selectivity within mixed cell populations. Similarly, SNAs coated with the dysopsonizing protein serum albumin show reduced macrophage uptake, providing a strategy for tailoring selective SNA delivery. Importantly, the protein coronae remain stable on the SNAs in human serum, exhibiting a less than 45% loss of protein through exchange after 12 h at 37 °C. Taken together, these results show that protein–SNA complexes and the method used to prepare them provide a new avenue for enhancing SNA stability, targeting, and biodistribution.